2004
DOI: 10.2337/diabetes.53.12.3239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyol Pathway Hyperactivity on Protein Kinase C Activity, Nociceptive Peptide Expression, and Neuronal Structure in Dorsal Root Ganglia in Diabetic Mice

Abstract: We explored the specific impact of polyol pathway hyperactivity on dorsal root ganglia (DRG) using transgenic mice that overexpress human aldose reductase because DRG changes are crucial for the development of diabetic sensory neuropathy. Littermate mice served as controls. Half of the animals were made diabetic by streptozotocin injection and followed for 12 weeks. After diabetes onset, diabetic transgenic mice showed a significant elevation of pain sensation threshold after transient decrease and marked slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…A larger percentage of DRG neurons stained positively for SP as compared with CGRP, and SP staining neurons nearly always co-expressed β2-AR. The DRG peptide staining patterns were similar to other recent reports [41,45].…”
Section: The Distribution Of Expression Of Cgrp and Sp In The Drgsupporting
confidence: 78%
“…A larger percentage of DRG neurons stained positively for SP as compared with CGRP, and SP staining neurons nearly always co-expressed β2-AR. The DRG peptide staining patterns were similar to other recent reports [41,45].…”
Section: The Distribution Of Expression Of Cgrp and Sp In The Drgsupporting
confidence: 78%
“…PKC␤ activity is increased in the DRG of diabetic compared with control mice (Uehara et al, 2004), phorbol esters that activate PKC increase nociceptive responsiveness in inflammatory pain (Coderre, 1992) and enhance thermal hyperalgesia in diabetic rats (Ohsawa and Kamei, 1999), and inhibition of PKC decreases hyperalgesia in STZ diabetic rats (Ahlgren and Levine, 1994), attenuates thermal hyperalgesia induced by partial sciatic nerve ligation, and attenuates opiateinduced antinociception in diabetic mice (Ohsawa and Kamei, 1997). Previous studies have suggested that PKC activation may modulate the electrophysiologic properties of tetrodotoxin (TTX)-sensitive and TTX-resistant voltage-gated sodium channels (Dascal and Lotan, 1991;Numann et al, 1991;Thio and Sontheimer, 1993), but this is the first report to demonstrate PKC-mediated regulation of voltage-gated sodium channel protein levels in primary sensory neurons in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 8 weeks of diabetes altered the unmyelinated Cfibers response, as seen by an increase of tail withdrawal latency, demonstrating hypoalgesia. Uehara et al (35) revealed that the pain sensation in diabetic mice was initially hyperalgesic, followed by late hypoesthesia in the presence of severe neuropathy. In diabetic patients, thermal hypoalgesia is associated with degenerative neuropathy, which includes the loss of epidermal C-fiber terminals (33,36).…”
Section: Discussionmentioning
confidence: 99%